Sonographic Detection of Nanoparticles used for Magnetic Drug Targeting - Fink, Michael; Ermert, Helmut; Löffler, Michael; Sutor, Alexander; Tewes, Barbara; Koch, Andreas; Alexiou, Christoph; Lyer, Stefan (Proceedings SENSOR 2015, 2015)

Ultrasonic defect detection in multi-material, axis-symmetric devices with an improved synthetic aperture focusing technique (SAFT) - Scharrer, Thomas; Koch, Andreas; Fendt, Karl; Rupitsch, Stefan; Sutor, Alexander; Ermert, Helmut; Lerch, Reinhard (2012 IEEE International Ultrasonics Symposium Proceedings, 2012)
This paper describes an improved synthetic-aperture-focusing-technique (SAFT) for ultrasonic defect detection in multi-material devices with a circular cylindrical geometry. In conventional SAFT, defect imaging resolution in such specimen is limited, due to refraction at material interfaces. Hence, the improved technique allows to increase the probability of detection (POD) and the resolution of defects in multi-material, axis-symmetric devices. Especially, if defects are located in layers far away from the device surface and the discrepancies in the speed of sound (SOS) of the specimen materials are thoroughly substantial, it is indispensable to implicate refraction effects in the SAFT processing. Thereby, the examination is divided into three major steps. First, a specimen is scanned by rotating a spherically focused immersion ultrasound transducer around it. In a second step, a corrected time of flight (TOF) distribution is calculated by a fast marching method (FMM) with the à-priori knowledge of the specimen layout and the different SOS in the materials. As third and last step, the improved SAFT is performed utilizing the TOF distribution. To verify improvements in comparison to a conventional SAFT, a specimen is inspected, consisting of a steel and a polyvinyl chloride (PVC) part. © 2012 IEEE.

Ultrasonic imaging of a turbine blade model using a 360° synthetic-aperture-focusing-technique and reverberation suppression - Scharrer, Thomas; Koch, Andreas; Rupitsch, Stefan; Sutor, Alexander; Ermert, Helmut; Lerch, Reinhard (2013 IEEE International Ultrasonics Symposium Proceedings, 2013)
In this contribution, we present a method to complement missing X-ray computed tomography (CT) data of irregular shaped metallic specimen, like turbine blades, by ultrasonic testing in immersion mode. Therefore, an adapted 360° synthetic-aperture-focusing-technique (SAFT) is used to obtain particular information of the inner pattern of the specimen. These structural information cannot be imaged by X-ray CT due to limited penetration in specific directions and consequently absent projections in the dataset. However, arising artifacts caused by refraction and signal reverberation impede the detection of the desired structural information by ultrasonic testing of those irregular metallic specimens. To cope with refraction effects caused by the immense discrepancies in speed of sound (SOS) at the interface of the couplant and the specimen, the approach is based on virtual source elements. Furthermore, the covering of near-surface structures by the first reflection signals is treated by a subspace based filtering approach and signal reverberation artifacts are suppressed by predictive deconvolution. © 2013 IEEE.